THE BUSINESS BEHIND THE BUSINESS: THE ROLE OF FINANCE IN THE DESIGN OF WEB SERVICES - Kripe, Zane (AoIR Selected Papers of Internet Research, 2014)
This article explores the production of internet services by looking at how web technology startups design their products and develop their business models. In particular, it explores how financial considerations of startups influence the types of digital services that become available to the internet users and under what terms. The research is based on an ethnographic study of investment seeking technology startups in Singapore and uses qualitative data gathered during participatory observation of startup entrepreneurs and investors. It argues that to a large extent the technology business is characterised by commodification at two levels. First, as the company develops its service into a commodity for its users and customers. Second, as the startup itself becomes a commodity for the venture capital* as it seeks to attract funding in the investment market. Exploration of this double relationship reveals how different regimes of value influence the social and material construction of the internet. This paper argues that for a better understanding of the contemporary internet landscape, the internet services have to be situated in their political economy relations and dependencies. In 2012 technology business portal TechCrunch featured an article on how Facebook has changed the design of its ‘App Permission Requests’ in a way that significantly downplays the privacy tradeoffs users agree to when engaging with apps. In the article such change in the interface design was explained as nearly self-evident: “After all, this access to our information and identity is the currency Facebook is trading in and what is driving its stock up or down.” (Charkham, 2012) Since the summer of 2012 the discussion of privacy and social media has clearly gone a long way. However, this Facebook example highlights also another, much less discussed aspect, namely, the active role financial considerations and venture capital plays in shaping the internet landscape. This aspect is to what I wish to turn the attention to in this paper.